The effects of the structure of local government on crime - Tapscott, C P G (Department of Political Studies, 2016)
It is the intention of this thesis to review the role of municipal government in Cape Town as a local planner - and as such as an agency entrusted with the welfare of its inhabitants - in terms of the general governing processes existent in South Africa. That is to say, in terms of the position it occupies in the infrastructure of government in the country, and its relationship and interactions with other levels of the governing pyramid. As a corollary of this, an attempt will be made to ascertain and measure the effectiveness of local government (in terms of its stated objectives), and relate such inadequacies as are found to be existent, to insufficiencies in the powers assigned to local bodies. The study itself is in five parts: - Part 1: A review of the early history of local government in England (the forerunner of the present South African system), and the development of general objectives. The identification of key objectives in local governments throughout the world today. A review of the early history of local government in South Africa traced through until the present, outlining its position and function in the governing process. Part 2: An analysis of local government in South Africa is represented in terms of the three basic objective identified in part 1. These are: 1) Local representation and participation. 2) Decentralised and effective administration, and as an outcome of these first two objectives, 3) provision for the welfare of the local population. Part 3: A brief review of social indicators was undertaken to attempt to quantify the effects of good or bad administration. Crime was chosen as an indicator of social malaise, and statistics cited to illustrate a deteriorating situation. Part 4: Case studies of three residential areas in Cape Town were undertaken to determine possible antecedents of crime. An attempt is made to relate the perpetuation of these antecedents to inadequate control at the local level brought about by a lack of power. Part 5: The final section establishes the importance of local government and concludes that a lack of administrative control at this level has inevitable consequences for social welfare standards. The section includes the proposal of various solutions for the restructuring of local authorities for the better administration of the metropolis. At the outset it must be emphasised that the investigation was undertaken without particular bias towards any specific form of local government. Nor was it felt that a high degree of local autonomy was a necessary prerequisite for successful government. What was intended however, was to establish the effectiveness of the system in the context of government in South Africa.